KINERJA KOMISI D DEWAN PERWAKILAN RAKYAT DAERAH PROVINSI RIAU TAHUN 2015 - Muhammad Afdal; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study entitled "Performance of Commission D of the Regional Representatives Council Riau Province Year 2015", the study is based on a Regulation of the DPRD Riau Province No 30 of 2014 on the Rules of Conduct DPRD Riau Province decisive concerning the composition, status, rights, duties, functions, powers , as well as fittings DPRD Riau Province. The regulation also mentioned about the duties and functions of the Commission D as fittings remain DPRD Riau Province is also implementing a legislative function, budgetary, and oversight. Issues contained in this thesis is about the still low and not maximal performance of Commission D in its function as a legislative body area. As a legislative function is not running, the budget function is not maximized, and the implementation of the supervisory function is still not achieve the targets that have been planned throughout 2015. The method used in this study is a qualitative method that describes the data descriptively. Data collection techniques used were interviews, observation and document tracking. While the source of the data used are primary data obtained from the test site and supported by secondary data.Based on the results of research conducted there are several factors inhibiting the performance of Commission D in their duties the internal and external factors.Keyword: Performance, Commission D DPRD Riau Province